DEVELOPMENT OF STANDARD OPERATIVE PROCEDURE FOR RAS POTTALI W.R.S. RASA PRAKASHA SUDHAKARA - Vijay Shree Bharti; Rajendra Barfa; Amit Mishra; Sakhitha K.S.; K. Shankar Rao (AYUSHDHARA, 2021)
Since medieval period, Rasashastra has occupied a pivotal position in Ayurvedic system of medicine. In Rasashastra, uses of Mercury as a medicine have evolved gradually over centuries. Compared to traditional Rasa formulations, Many of them which were earlier in practice are not at all used today. Though literature is available on quality aspects of such herbo-mineral formulations in the classical text books, contemporary science is raising concerns at regular intervals on herbo-mineral formulations. Thus, it becomes mandate to develop quality profiles of all formulations that contain metals or minerals in their composition. ‘Rasa Pottali’ is one of such preparation that is grouped under ‘Murchita Parada Yoga’ in consolidate form which also incorporates the Pota Bandha of Parada. No other classical references are found for this formulation except for Rasa Prakasha Sudhakara. In the present study an attempt has been made to prepare Rasa pottali by classical reference and to evaluate its manufacturing process with possible modifications. As per the SOP, the formula mentions that the application of Dhatura patra swarasa to be applied on Pottali covered with cloth but this seems to be not appropriate for the Pharmaceutical preparation and to develop SMP of this preparation. Keeping this in view, the preparation has designed into three different experiments and are carried out to prepare three samples of Rasapottali RP1 (7-7 Bhavana with Tamboola patra swarasa and Dhatura parta swarasa), RP2 (7 Bhavana with Tamboola patra swarasa and 7 Lepana with Dhatura patra kalka) and RP3 (7 Lepana with Tamboola patra kalka and 7 Lepana with Dhatura patra kalka).